2021
DOI: 10.1038/s41598-021-97347-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell polarity and cell adhesion associated gene expression differences between invasive micropapillary and no special type breast carcinomas and their prognostic significance

Abstract: Invasive micropapillary carcinoma of the breast (IMPC) has been in the focus of several studies given its specific histology and clinicopathological course. We analysed mRNA expression profiles and the prognostic value of 43 genes involved in cell polarity, cell-adhesion and epithelial–mesenchymal transition (EMT) in IMPC tumors and compared them to invasive breast carcinomas of no special type (IBC-NST). IMPCs (36 cases), IBC-NSTs (36 cases) and mixed IMPC-IBC NSTs (8 cases) were investigated. mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 71 publications
(77 reference statements)
5
10
0
Order By: Relevance
“…Significant differences have been identified in mRNA expressions of integrin-β1 (ITGB1), integrin-α1 (ITGA1), RAC1, CLDN1, SLUG/SNAI2, ZEB1, DLG1, CLDN4, CDH1 (E-cadherin), OCLN, CLDN7, AFDN/ AF6, CLDN3, LIN7A which are effective in cell polarity in MPCs (Table 3). 59,60 Integrin is a protein that forms the glandular lumen and maintains polarity in epithelial cells. Its aberrant expression is associated with adhesion, angiogenesis, tumor progression, and metastasis.…”
Section: Mrna Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant differences have been identified in mRNA expressions of integrin-β1 (ITGB1), integrin-α1 (ITGA1), RAC1, CLDN1, SLUG/SNAI2, ZEB1, DLG1, CLDN4, CDH1 (E-cadherin), OCLN, CLDN7, AFDN/ AF6, CLDN3, LIN7A which are effective in cell polarity in MPCs (Table 3). 59,60 Integrin is a protein that forms the glandular lumen and maintains polarity in epithelial cells. Its aberrant expression is associated with adhesion, angiogenesis, tumor progression, and metastasis.…”
Section: Mrna Expressionmentioning
confidence: 99%
“…Claudins are integral membrane proteins, and CLDN1, CLDN3, CLDN4, and CLDN7 significantly lower expression levels are shown in IMPC cases. 59 The Crumbs complex plays an essential role in the apical polarity complex. PALS (proteins associated with LIN7) and PATJ (Pals1-associated tight junction) are the proteins that make up this complex.…”
Section: Mrna Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Kramer et al showed that IMPC tumor cells were in a highly epithelial state and did not use the EMT pathway, but rather form cell clusters during invasion and metastasis. 82 …”
Section: Lymphovascular Invasion and Lymph Node Involvementmentioning
confidence: 99%